2014
DOI: 10.1097/jom.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Determinants of Cumulative Lead Exposure

Abstract: Objectives To examine the relation between occupation and cumulative lead exposure—assessed by measuring bone lead—in a community-dwelling population Method We measured bone lead concentration with K-shell X-Ray Fluorescence in 1,320 men in the Normative Aging Study. We categorized job titles into 14 broad US Census Bureau categories. We used ordinary least squares regression to estimate bone lead by job categories adjusted for other predictors. Results Service Workers, Construction and Extractive Craft Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, most NAS participants, having lived in the era of leaded gasoline combustion and being veterans, were exposed to both environmental and occupational lead levels throughout their life-course and thus may reflect exposure trajectories of millions of employees in general industry and construction. 40 Other limitations include the use of DNA methylation to impute white blood cell distribution, and residual confounding by cell type distribution could still remain. However, the state of the art method we applied has been shown to accurately reflect leukocyte distribution, especially with an adult reference methylome 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most NAS participants, having lived in the era of leaded gasoline combustion and being veterans, were exposed to both environmental and occupational lead levels throughout their life-course and thus may reflect exposure trajectories of millions of employees in general industry and construction. 40 Other limitations include the use of DNA methylation to impute white blood cell distribution, and residual confounding by cell type distribution could still remain. However, the state of the art method we applied has been shown to accurately reflect leukocyte distribution, especially with an adult reference methylome 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the positive correlation with age may occur because older children tend to play more outdoors, increasing their contact with soil particles with greater respiratory demand, and beside that Pb is a cumulative toxic heavy metal that is deposited in bones. Ji et al [ 41 ] observed that workers in occupations such as construction and extractive craft workers, and installation, maintenance, and repair craft had the highest bone lead concentrations. In our cohort, only 10% of the children’s fathers had occupational activities related to the ones reported above, which could have some role on children’s Pb exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The study participants who worked in the automotive industry reported experiencing muscle pain, fatigue, irritation, and decreased haemoglobin and red blood cell counts after prolonged exposure to lead (Dongre et al 2011). The effects of lead exposure on the health of people who work in the printing industry were the subject of a case study by Ji et al (2014). Symptoms, including convulsions, diarrhoea, anaemia, colic, nephritic discomfort, and leg pain, were linked to prolonged exposure to lead dust in printing presses.…”
Section: Lead Exposure Through Ayurvedic Preparationsmentioning
confidence: 99%